PELATIHAN PENGELOLAAN BISNIS SYARIAH PADA PELAKU UMKM DI DESA WISATA BANJARAN - Febrian Wahyu Wibowo; Abdul Salam; Ahmad Yunadi; Al Haq Kamal; Rusny Istiqomah Sujono; Baiq Ismiati; Abi Suryono; Abdullah Yahya; Mu’inan Rafi (Jurnal Abdi Insani, 2023)
The emergence of MSMEs or new businesses in an area, this certainly makes business competition. Business competition triggers business people to make strategies in business management in order to have good performance. In Islam, the Prophet is a role model for doing business in an Islamic way. His success in managing a business can be used as a lesson that needs to be applied in doing business today. It is hoped that the application of Sharia business values in their business, by providing training programs related to Sharia business management, is hoped to provide understanding and instill Sharia Business values in MSME actors. The purpose of carrying out this activity is to provide insight and understanding regarding good business management from a Sharia point of view, bearing in mind that in the Banjaran Kaluahan Guwosari tourist village there are many MSME actors and the great potential that exists in the area. The technical training method is interaction between participants and presenters and presenting case study materials on problems in MSMEs so that the material presented can be directly applied by the participants and of course it is easier to understand. This activity was carried out in stages by giving direct seminars to MSME actors and providing strategic practices delivered by all speakers. During the implementation of the event, there were many problems faced by MSME actors, especially in terms of business management. At the end of the event, several things were found that could later be developed by MSME actors and the community in the Banjaran Tourism Village, Kalurahan Guwosari, as follows; Development of Educational and Historical Tourism Villages, Creation of Sharia corner websites for Sharia business consulting media by MSME actors, Implementation of advanced training to maximize the plans that have been formed, and Creation of joint accounts as a forum for investment and paid marketing fees for MSME actors in Banjaran Tourism Village. This activity is sustainable and can unravel various other problems that exist in the Banjaran Tourism Village, Kalurahan Guwosari so that existing problems can be resolved properly and get maximum results.